Analisis Tingkat Kepuasan Masyarakat Terhadap Pembangunan Jembatan Di Desa Bulukandang - Hamida, Wanda; ., Khofifah (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Bulukandang Bridge, which connects Bulukandang Village and Ketanireng Village, was reconstructed to improve public safety and accessibility. To assess the success of this development, it is important to evaluate the level of community satisfaction as the direct users of this infrastructure. This study employs a quantitative descriptive approach using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. Data were collected through questionnaires distributed to 95 respondents living around the bridge area. The analysis focused on five main indicators: construction quality, safety and security, comfort, traffic flow, and aesthetics. The results show that the community’s satisfaction level with the construction of Bulukandang Bridge falls into the